An unusual case with vasculo-Behçet's disease: peripheral arterial aneurysm in an elderly woman - (:unkn) unknown (My University, 2014)
Behçet's disease (BD) is a chronic, multi-systemic disorder that can affect all sizes of arteries and veins. Vascular involvement of BD is generally observed in young men and is an important cause of morbidity and mortality. Arterial lesions can appear as aneurysms, stenosis and occlusions in BD. We, here, present the case of a woman who developed a peripheral arterial aneurysm in her sixth decade, 20 years after disease onset. BD patients with aneurysms should be consulted at any age for pre- and post-operative assessment for immunosuppressive treatment to reduce recurrences, complications and disease activation.
Keywords: Female; Humans; Behcet Syndrome; Aged; Fibrosis; Age of Onset; Angiography; Aneurysm; Femoral Artery